2017
DOI: 10.1186/s13046-017-0652-8
|View full text |Cite
|
Sign up to set email alerts
|

Smoldering mantle cell lymphoma

Abstract: BackgroundMantle cell lymphoma (MCL) is an aggressive disease, with poor prognosis and a limited survival. However, some patients with indolent MCL can survive beyond 7~10 years. These patients remain largely asymptomatic and can be in observation for a long time without any treatment. The process of “wait and watch” leaves these patients with the potential risk of evolution to classic, aggressive MCL. On the other hand, early treatment for these patients may not impact overall survival but rather affects the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 105 publications
0
24
0
1
Order By: Relevance
“…[59] In addition, since EGCG decreased constitutive activity of GPRC6A, it might also be considered an inverse agonist at high concentrations. Since GPRC6A regulates T production and PCa progression, [44,60] the inhibitory effects on GPRC6A are consistent with known effects of EGCG to suppress T, [60] and would also provide a mechanism to account for EGCG reduction in PCa risks. Future studies in preclinical models will be needed prove that the beneficial effects of green tea on PCa progression is mediated by EGCG inhibition of GPRC6A.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…[59] In addition, since EGCG decreased constitutive activity of GPRC6A, it might also be considered an inverse agonist at high concentrations. Since GPRC6A regulates T production and PCa progression, [44,60] the inhibitory effects on GPRC6A are consistent with known effects of EGCG to suppress T, [60] and would also provide a mechanism to account for EGCG reduction in PCa risks. Future studies in preclinical models will be needed prove that the beneficial effects of green tea on PCa progression is mediated by EGCG inhibition of GPRC6A.…”
Section: Discussionmentioning
confidence: 59%
“…[36,43] Ablation of GPRC6A attenuates, whereas Ocn administration exacerbates, PCa progression in xenograft models. [44] In this study, we used a combination of functional studies and computational molecular dynamics-based docking using structural models of both VFT and 7-TM domains to investigate the effects of GA and EGCG on GPRC6A activation.…”
Section: Doi: 101002/mnfr201700770mentioning
confidence: 99%
“…The clinical course of MCL (Table ) can be smoldering nodal/extra‐nodal or asymptomatic non‐blastoid leukemic non‐nodal, and these clinical variants (about 10%‐20% of MCL cases) generally do not need immediate systemic treatment, meaning the watch‐and‐wait strategy is safely pursued. On the other hand, most MCL patients (70%‐80% of MCL cases) present with symptomatic lymphadenopathy or symptomatic extra‐nodal disease requiring systemic therapy.…”
Section: Clinical Presentation Diagnostic Approach and Advances In Tmentioning
confidence: 99%
“…The expression of CD23 is closely associated with CD200 expression. Ye H et al 5 reported similar findings and referred to such cases as smoldering mantle cell lymphoma. CD200 is an important marker of CLL/SLL in the differential diagnosis from other CD5-positive indolent lymphomas.…”
Section: Differential Diagnosis: Mantle Cell Lymphomamentioning
confidence: 68%